Forming of communicative competence as condition of professional preparation of future teachers of physical culture - Samsutina NM (Kharkov National Pedagogical University, 2010)
The modern state and necessity of realization of forming communicative competence of future teachers of physical culture is found out in the process of professional preparation. 294 students took part in an experiment. Rotined expedience of realization of forming of communicative competence of future teachers of physical culture. The questionnaire of students of higher educational establishments is conducted. The level of formed of communicative competence for students remains at low level. It needs strengthening of attention to perfection of process of professional preparation of future teachers of physical culture.